2013
DOI: 10.1002/elan.201300103
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Natural Dissolved Concentration of Zirconium in Seawater by Adsorptive Stripping Voltammetry

Abstract: A voltammetric method was developed for zirconium determination as Zr(IV)-cupferron-oxalate-diphenylguanidine complex based on adsorptive accumulation at the HMDE (E peak = À0.95 V). The supporting electrolyte was a mixture of acetate/acetic acid (pH 4.6) and ammonium acetate (pH 5.7) solutions. E ads = À0.6 V (vs. Ag/AgCl), t ads = 400 s, 10 mV s À1 scan rate, and DP mode were the main parameters. The linear range was 0.033 to 3.3 10 À9 mol L À1, and the LOD and LOQ (t ads = 400 s) were 0.77 and 1.6 10 À11 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…In a previous study 29, it has been shown that Zr(IV) could be determined more stably (without peak vanishing) when the electrolyte solution contains oxalic acid and 1,3‐diphenylguanidine mixed with cupferron (COD mixture). In the present study, the COD mixture was investigated to assay V(V) and Zr(IV).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study 29, it has been shown that Zr(IV) could be determined more stably (without peak vanishing) when the electrolyte solution contains oxalic acid and 1,3‐diphenylguanidine mixed with cupferron (COD mixture). In the present study, the COD mixture was investigated to assay V(V) and Zr(IV).…”
Section: Resultsmentioning
confidence: 99%
“…Voltammetric determinations of Zr(IV) as well as V(V) at trace levels are more properly done as complexes of organic compounds 1428. In a previous paper 29 the adequacy of some of these ligands towards the Zr(IV) determination in natural waters was critically discussed. The ligand COD showed the best results for Zr(IV) determination at trace levels.…”
Section: Introductionmentioning
confidence: 99%
“…Various analytical techniques used for the determination of zirconium in different matrices include spectrophotometry [6], fluorescence spectrophotometry [7], atomic absorption spectrometry [8], inductively coupled plasma atomic emission spectrometry [9], inductively coupled plasma mass spectrometry [10], isotope dilution mass spectrometry [11], X-ray fluorescence [12], neutron activation analysis [13], proton activation analysis [14], potentiometry [15], kinetic potentiometry [16], polarography [17], stripping voltammetry [18,19], impedimetry [20], and liquid chromatography [21].…”
Section: Introductionmentioning
confidence: 99%